(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Total 54 fertilizer samples were randomly collected from the markets of four districts ofBangladeshto assess nutrient and heavy metal (Cd, Cr & Pb) contents in different fertilizers. The chemical analyses of fertilizers were conducted at the Department of Agricultural Chemistry,BangladeshAgriculturalUniversity, Mymensingh. Nutrient status of fertilizers was determined using the standard procedures and heavy metals in the fertilizer extract were analyzed using Atomic Absorption Spectrophotometer (AAS). Nitrogen (N) content in urea collected from different areas ranged from 41.37 to 46.27%. Biuret content of the collected urea samples varied from 1.40 to 2.80%, where the maximum allowable limit (MAL) is 1.50%. Among the six urea samples, biuret content exceeded the MAL in five samples. Phosphorous (P) content in most of the triple superphosphate (TSP) samples was higher than the specified amount. Out of eight samples, only two samples contained less than 20% P. Out of eight diammonium phosphate (DAP) samples, only three samples contained lower amount of P than the specified amount and five samples contained lower amount of N than the specified amount. Chromium content in all theDAPsamples were much higher than the MAL. Potassium (K) content in all five collected muriate of potash (MoP) samples were lower than the specified amount with an average of 45.81% K. The concentration of sulphur (S) in fertilizer samples in the investigated area varied from 16.50 to 21.60%. Out of six magnesium sulphate samples, five samples contained lower than the specified amount (9.5%) of Mg. The concentration of boron (B) in solubor samples varied from 13.55 to 19.56%, which are lower than the standard limit (20.90%). The concentration of zinc (Zn) in all the collected zinc sulphate heptahydrate samples had lower amount of Zn than the standard limit (23%). Only one out of six collected copper sulphate samples, met the specified limit of Cu (25.40%). Total 42 fertilizer samples (77.80%), out of 54, had less than the specified amount of nutrients. Heavy metals like Pb and Cr content exceeded the MAL in 67% and 47% of collected fertilizer samples, respectively. Cadmium content was below the detectable limit of flame in AAS in all the samples. In order to minimize the impact of fertilizer adulteration on food security and safety, continuous monitoring of fertilizer quality is required. J. Bangladesh Agril. Univ. 15(2): 219-225, December 2017